2013
DOI: 10.2147/ijn.s51756
|View full text |Cite
|
Sign up to set email alerts
|

3-aminopropyl functionalized magnesium phyllosilicate as an organoclay based drug carrier for improving the bioavailability of flurbiprofen

Abstract: This study aimed to develop an oral delivery system using clay-based organic–inorganic hybrid materials to improve the bioavailability of the drug, flurbiprofen, which is poorly soluble in water. 3-aminopropyl functionalized magnesium phyllosilicate (AMP clay) was synthesized by a one-pot direct sol-gel method, and then flurbiprofen (FB) was incorporated into AMP clay (FB-AMP) at different drug/clay ratios. The structural characteristics of AMP and FB-AMP formulation were confirmed by X-ray diffraction, Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Aminoclay was prepared by the method reported by Yang et al. ( 2013 ). Acetone was purchased from Daejung chemical & metals Co., Ltd. (Gyeonggi-Do, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aminoclay was prepared by the method reported by Yang et al. ( 2013 ). Acetone was purchased from Daejung chemical & metals Co., Ltd. (Gyeonggi-Do, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Aminoclay is delaminated to cationic and water soluble nanosheets in water. Aminoclay can enhance the solubility of acidic drugs by modulating the microenvironmental pH to more basic (Yang et al., 2013 ; Yang et al., 2016 ). In addition, aminoclay can control the drug release by interacting with negatively charged drug and/or polymers (Holmström et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…ACNs are layered materials composed of magnesium phyllosilicate functionalized with aminopropyl groups [1,2] (Figure 1A). Although it has been previously reported that ACNs exhibit low toxicity in human lung and skin fibroblast cell lines [1], whether ACNs can modulate the immune system remains largely unknown.…”
Section: Acn Treatment Attenuates Basal Levels Of Immunogenicity Of R...mentioning
confidence: 99%
“…Aminoclay nanoparticles (ACNs), one of the drug carriers that can be orally administered, are synthetic organic-inorganic layered materials delaminated to water-soluble cationic nanosheets in water [1]. ACNs with a positive charge can interact with negatively charged drugs to produce drug-ACN complexes, which enhance the dissolution and absorption rates of poorly water-soluble drugs such as flurbiprofen and telmisartan in the gastrointestinal tract [2,3]. Furthermore, ACN-based carrier systems can be employed for delivering insulin to the intestine [4].…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacological effects of steroidal anti-inflammatory drugs are attributed to the inhibitory effects of NF-κB, either by direct interaction with the NF-κB p65 subunit (4) or by increasing transcription of its inhibitor (I-κB-α) (5). Pharmacokinetic data on flurbiprofen has been studied in various animal models and humans (6,7); however, it is well absorbed orally, reaching a maximum concentration in the blood in approximately 1.5 hours (range 0.5-4 hours) (8,9). Flurbiprofen was eliminated within 24 hours of the last administered dose (10).…”
Section: Introductionmentioning
confidence: 99%